Stem cell markers: A guide to neoadjuvant therapy in breast carcinomas - Zuhal Gucin; Nur Buyukpinarbasili; Melin Ozgun Gecer; Yeliz Emine Ersoy; Haci Mehmet Turk; Seyma Yildiz; Direnc Ozlem Aksoy (Indian Journal of Pathology and Microbiology)
Aim: This study aims to investigate potential associations between the stem cell population and the degree of tumor regression in breast carcinomas treated with neoadjuvant therapy. Settings and Design: The study included 92 patients with breast carcinoma who received neoadjuvant therapy. Tumor regression was defined based on Miller and Payne grading system. Patients with grade 1 or 2 regression on a 5-point scale were included in group 1 (n = 37), grade 3 regression in group 2 (n = 32), and grade 4 or 5 regression in group 3 (n = 23). Materials and Methods: Immunohistochemical staining was performed on paraffin block sections of every case using CD44, CD24, CD29, CD133, ID4, and ALDH1 antibodies to detect stem cells. Statistical Analysis Used: IBM Statistical Package for the Social Sciences (SPSS), version 23.0 (IBM Corp., Armonk, NY, USA) software was used for statistical analyses, and a P value less than 0.05 was considered statistically significant. Results: Histologically high-grade tumors are more common in the near-complete/complete response group (P = 0.004). HER2-positive tumors were more common in the complete/near-complete response group (P = 0.054). Tumor cells positive for stem cell markers CD44 and CD24 were more common in the poor response group (P = 0.027 and P = 0.001, respectively). CD29 expression was reduced in the posttreatment residual tumor tissue in the near-complete/complete response group. Conclusion: High CD44 and CD24 expression may be a predictor of poor response/nonresponse to neoadjuvant therapy in breast carcinomas. Background: In recent years, stem cells have been defined as the main cell population responsible for resistance to anticancer therapies.